THE EFFECT OF SELF-EFFICACY ON MATHEMATICAL COMMUNICATION ABILITY OF JUNIOR HIGH SCHOOL STUDENTS ON THE PYTHAGOREAN THEOREM - Andriana Siwi Purwandari; Rippi Maya ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2019)
Abstract This study aims to analyze and examine the mathematical communication ability that are influenced by junior high school students self-efficacy. The method in this study uses a correlational method with quantitative approach. The population in this study were students of junior high school in Cimahi City, with a sample of 36 students who were determined by purposive sampling technique at one of junior high school in Cimahi City. The instrument used in this study is a communication ability test that consisting of 5 essays and a students’ self-efficacy scale that consisting of 25 statements scales. The results showed that students communication ability was positively influenced by self-efficacy of 19.1%, while 80.9% was influenced by factors other than students’ self-efficacy. The correlation between self-efficacy and mathematical communication skills of students is included in the medium category. Keywords:  Mathematical Communication, Self-Efficacy